1 REGULATION OF LKB1-DEPENDENT ADENOSINE MONOPHOSPHATE-ACTIVATED PROTEIN KINASE BY PROTEIN KINASE C-z R. (1st January 2006) - Xie, Z.; Davis, B.; Zhang, M.; Zou, M-H
Abstract : We previously reported the PI-3 kinase-dependent activation of the 59-AMP-activated kinase (AMPK) by peroxynitrite (ONOO 2 ) and hypoxia-reoxygenation (H/R) in cultured endothelial cells. Here we show the molecular mechanism of activation of this pathway involves atypical protein kinase C (PKC)-z, a known downstream enzyme of PI-3 kinase, which leads to AMPK activation via LKB1. Exposure of bovine aortic endothelial cells (BAEC) to ONOO 2 significantly increased the phosphorylation of both Thr172 of AMPK and the Ser1179 of endothelial nitric oxide synthase (eNOS), a known downstream enzyme of AMPK. In addition, activation of AMPK by ONOO 2 was accompanied by increased phosphorylation of PKC-z (Thr410/403) and translocation of cytosolic PKC-z into the membrane. Further, inhibition of PKC-z with either pharmacological (PKC-z pseuosubstrates, PKC-z-PS) or genetic inhibitors (PKC-z dominant negative mutants, PKC-z-DN) abrogated ONOO 2 -induced AMPK-Thr172 phosphorylation as that of eNOS. Furthermore, overexpression of a constitutively active PKC-z mutant (PKC-z-CA) enhanced the phosphorylation of AMPK-Thr172, suggesting that PKC-z is upstream of AMPK activation. In contrast, ONOO 2 activated PKC-z in LKB1-deficient Hela-S3 but affected neither AMPK-Thr172 nor AMPK activity. These data suggest that LKB1 is required for PKC-z-enhanced AMPK activation. In vitro, recombinant PKC-z phosphorylated both LKB1 at Ser428, resulting in phosphorylation of AMPK at Thr172. In several cell types originating from human, rat, and mouse, inhibition of PKC-z significantly attenuated the phosphorylation of both LKB1-Ser428 and AMPK-Thr172 that were enhanced by ONOO 2 . Taken together, we conclude that PKC-z can regulate AMPK activity by increasing the Ser428 phosphorylation of LKB1, resulting in association of LKB1 with AMPK and consequent AMPK Thr172 phosphorylation by LKB1.